Sunnhemp Seed Production Technology - Sarkar, S. K. (Indian Farming, 2018)
The importance of sunnhemp is regaining due to its biodegradable fibres as well as green manuring properties. Non-availability of quality seed is a major limiting factor for the expansion of this crop.